Monetary financing of public investment: a viable way forward for the euro area? - Andrew Watt (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
This article poses the question of whether monetary financing of public investment constitutes a viable way forward for the euro area. The problems of low inflation, high unemployment and public debts seem scarcely resolvable in an environment that is constrained by the virtual exhaustion of monetary policy and legal limitations on expansionary fiscal policy. The author draws on the literature on monetary finance to identify key features of a scheme that could function in the context of EMU. He proposes to achieve an indirect monetary financing of public investment by the ECB committing to take newly issued EIB bonds on to its balance sheet. This would be essentially costless in a deflationary environment and could be expected to exhibit high multiplier effects. The independence of the ECB is maintained by making bond purchases subject to an inflation 'trigger'.
Keywords: E02; E12; E22; E24; E31; E58; E62; E63; H54; H63; 330; monetary finance; monetary policy; public investment; euro area; ECB; EIB